Influência do ambiente alimentar comunitário no entorno da residência no consumo de ultraprocessados entre escolares - Raphaela Silveira Fraga (2020)
Introduction: The food environment can influence the choices of children and adolescents with a potential impact on food consumption. In the residential environment, the access and type of the food outlets might be one of the factors associated with unhealthy eating habits in this public. Objective: To evaluate the association between the residential community food environment and the consumption of ultra-processed foods among students in a Brazilian metropolis. Methods: A systematic review was conducted with the search for articles published between 2008 and 2018 in the PubMed, Scopus and BVS databases. Additionally, a crosssectional study was carried out with students (n = 708) aged 9 to 10 years from municipal schools in Belo Horizonte / MG. Socioeconomic information was obtained via telephone through a questionnaire with parents. Two 24-hour recalls were applied to the children and the consumption of ultra-processed foods was considered excessive when ≥ 80th percentile of the distribution. The objective measures of the community environment were density and proximity to food outlets that sells predominantly fresh or minimally processed (MP) food, predominantly selling ultra-processed (UP) and mixed foods. Additionally, the index of predominant UP and MP sales outlets was assessed. The geographical unit chosen was the Euclidean buffer of 1000 meters in the child's residential surroundings. Results: In the review, 17 studies were identified, the majority (94%) carried out in developed countries and published between 2011 and 2018 (86%). More than 80% of the studies showed two to three failures indicating limited methodological quality. The geographic information system was the predominant method to characterize the environment (94%) and almost all publications used secondary data from the environment (n = 16). Most studies (86.4%) found zero associations between the food environment and consumption and some found associations that were inverse to what was expected. Indexes that jointly assessed food outlets and food consumption showed more consistent results than isolated measures. In the cross-sectional study, it was found that children who lived in places with a predominance of ultra-processed selling establishments had a higher chance of consuming these foods (OR: 2.16; 95% CI: 1.21- 3.86), especially among those who did not study full time (OR: 3.10; 95% CI: 1.37-7.02) and those with lower economic income (OR: 3.09; 95% CI: 1.34-7.16). Conclusion: Inconsistent evidence was identified between the association of the food environment and consumption in the review conducted, probably due to the limited methodological quality of the studies, denoting the need for more robust assessments. In the cross-sectional study, there was a greater chance of consuming ultra-processed foods among schoolchildren living in places with a predominance of establishments selling these foods. Not studying full-time and belonging to low-income families increased the association between environment and food consumption. Thus, public policies and interventions are needed to expand access to establishments selling healthy food to the detriment of ultra-processed retail locations, especially in the most vulnerable regions, besides the appreciation of the school shift.